Influences of maternal reflective functioning on adolescents' psychosocial adjustment: The mediating role of adolescent's reflective functioning. - MinKyoung Park; Hyunjoo Song (PLoS ONE)
This study examines the relationship between maternal reflective functioning and adolescents' reflective functioning and psychosocial adjustment. In Study 1, The Parental Reflective Functioning Questionnaire for Adolescents (PRFQ-A) and Reflective Functioning Questionnaire for Youth (RFQ-Y), multidimensional scales used to assess reflective functioning in parents and adolescents, respectively, were validated in groups of Korean adolescents and mothers. In the results, the three factors were extracted (non-mentalizing, certainty, interest/curiosity) that were similar to those from the original version of the scale. However, the items comprising the interest/curiosity factor of the Korean validated RFQ-Y differed from the original scale. Both the reliability and validity of the scale were confirmed. Study 2 examined the mediating effects of adolescent reflective function on the relationship between parental reflective functioning and adolescent psychosocial adjustment. The structural equation modeling showed a good fit for all three models (adolescents' uncertainty/confusion, certainty, and interest/curiosity). However, some mediating effects of adolescents' reflective function were not confirmed. In conclusion, the results indicate that maternal reflective function influences the adolescents' psychosocial function through the mediating factor of adolescent reflective function, Unexpectedly, maternal interest/curiosity did not have a significant effect on adolescents' reflective function and psychosocial adjustment. Based on the results, altering Korean mothers' parenting attitudes may have a positive effect on adolescents' psychosocial adjustment. This work highlights that further research is needed to understand parent-child relationships in terms of reflective functioning, taking into account the influence of cultural context.